Tertullian’s Case for the Christiani Creatoris in Adversus Marcionem - Pierce, Alexander H. (Journal of theological interpretation, 2022)
In offering a close reading of Tertullian’s Adversus Marcionem 3-4, the present essay contends that Tertullian supports his belief that Christians are the proper continuation of God’s people in history by making a case for Christian separation from the Jews as the fulfillment of scriptural prophecy. Tertullian’s reading of the Creator’s Scriptures is his exegetical basis for forming a logic of separation between Christians and the chosen Jewish nation. This differentiation does not require an ontological bifurcation of the Creator and the God revealed in Jesus. Rather, God the Creator and Father of Jesus reveals this distinction in the operation of his providence in history and in Scripture. It is in this very separation that Christians fulfill the prophecies of the Creator God of the Hebrew Bible and religion.